The neuropeptide calcitonin gene-related peptide (CGRP) prevents inflammatory liver injury in mice - Kroeger, Irena; Erhardt, Annette; Abt, Dominik; Fischer, Michael; Biburger, Markus; Rau, Thomas; Neuhuber, Winfried; Tiegs, Gisa (Journal of Hepatology, 2009)
Background/Aims: Calcitonin gene-related peptide (CGRP) is a potent vasodilator and supposed to be responsible for neurogenic inflammation involved in migraine. Its role in inflammatory diseases of other organs is controversial and poorly investigated regarding liver inflammation, although the organ is innervated by CGRP containing primary sensory nerve fibers. Methods: Male Balb/c and IL-10 mice were pretreated with either αCGRP or the CGRP receptor antagonists CGRP or BIBN4096BS. Immune-mediated liver injury was induced by administration of lipopolysaccharide (LPS) or tumor necrosis factor-α (TNFα) to galactosamine (GalN)-sensitized mice and evaluated by serum transaminase activities and cytokine levels. Furthermore, intrahepatic CGRP receptor expression and hepatic CGRP concentrations were examined. Results: CGRP receptor 1 was expressed by immune cells and hepatocytes in human and murine liver. During liver injury CGRP receptor expression was increased whereas hepatic CGRP concentrations concomitantly decreased. While CGRP receptor antagonists failed to affect liver damage, pretreatment with αCGRP protected mice from GalN/LPS-induced liver injury by suppression of the pro-inflammatory cytokine response independently from IL-10 but related to the induction of the transcriptional repressor inducible cAMP early repressor (ICER). In contrast, αCGRP failed to protect against GalN/TNFα-induced liver failure. Conclusion: In the liver, CGRP exerts anti-inflammatory properties, which are characterized by a reduced production of pro-inflammatory cytokines. © 2009 European Association for the Study of the Liver.
Keywords: Calcitonin gene-related peptide; Inducible cAMP early repressor; Interleukin-10; Liver inflammation; TNFα